2014
DOI: 10.1016/j.placenta.2014.06.373
|View full text |Cite
|
Sign up to set email alerts
|

Macrosomia has its roots in early placental development

Abstract: Introduction We sought to determine if early placental size, as measured by 3-dimensional ultrasonography, is associated with an increased risk of delivering a macrosomic or large-for-gestational age (LGA) infant. Methods We prospectively collected 3-dimensional ultrasound volume sets of singleton pregnancies at 11–14 weeks and 18–24 weeks. Birth weights were collected from the medical records. After delivery, the ultrasound volume set were used to measure the placental volume (PV) and placental quotient (PQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
0
25
2
1
Order By: Relevance
“…The insulin growth factor II secreted by the obese pregnant women stimulates the placental growth [1]. A large size placenta in the first trimester of pregnancy allows a bigger nutrient transfer, and this rate of exchange remains throughout the whole pregnancy [3].…”
Section: Prenatal Diagnostic Of Macrosomiamentioning
confidence: 99%
“…The insulin growth factor II secreted by the obese pregnant women stimulates the placental growth [1]. A large size placenta in the first trimester of pregnancy allows a bigger nutrient transfer, and this rate of exchange remains throughout the whole pregnancy [3].…”
Section: Prenatal Diagnostic Of Macrosomiamentioning
confidence: 99%
“…Several epidemiologic studies have focused on this condition, and have identified a number of risk factors for macrosomic births. These encompass preexisting maternal diabetes, maternal age over 40 years, multi-parity, high pre-gravid body mass index (BMI ≥ 25 kg/m²), maternal height (≥165 cm), excessive gestational weight gain (GWG), male sex, prolonged gestation (>41 weeks), placental factors, parental non-smoking status, preexisting gestational diabetes, maternal obesity/overweight, and lifestyle behaviors [5]. Although macrosomia's risk factors have been well studied, the reasons behind it are still complex and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the analysis restricted to healthy mothers with normal BMI and without gestational diabetes, a discrepancy of at least 7 days was still associated with a 70 and 110% increased risk of severely LGA birth and macrosomia, respectively. Our findings suggest that accelerated fetal growth may start early in pregnancy and be present among normal‐weight mothers and when clinical signs of gestational diabetes are absent .…”
Section: Discussionmentioning
confidence: 77%